Po prostu rozsądek, czyli etyka dziennikarska - Bekrycht, Hubert (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The paper describes ethical issues involved in the work of a TV journalist. The author – an experienced editor and producer of TV programs – diagnoses the condition of today’s media and describes concrete cases in which ethical standards were violated. The examples that he describes – like journalists leading political meetings or unreliable commenting on the controversial actions of national and local politicians – arise in his opinion as the result of the “egoistic and consumerist mentality of young journalists” rather than a lack of education.